(untitled) (Journal of Forensic Medicine & Toxicology, 2023)
Introduction: The economic impact of the lockdown to restrict the spread of the virus during the COVID-19 pandemic has been tremendous. Each suicide is a traumatic event that takes an individual’s life abruptly and has a long-term rippling impact on the lives of family, friends, and communities. One of the most uncommon methods of suicide is electrocution. Case: A 26-year-old man was found dead in a hotel room with bare wire encircling his left wrist and right great toe connected to a wall plug carrying a 220 V current. He had been suffering from a depressive illness for some time. The Medico-legal autopsy and other findings attributed death due to suicidal electrocution. Conclusion: In this case, a young adult used an unusual method to end his life. With the help of a comprehensive police investigation and appropriately analyzed circumstantial evidence, the dilemma in the manner of death could be solved.